Convergence of a Singular Euler-Maxwell Approximation of the Incompressible Euler Equations - Jianwei Yang; Hongli Wang (Journal of Applied Mathematics)
This paper studies the Euler-Maxwell system which is a model of a collisionless plasma. By energy estimation and the curl-div decomposition of the gradient, we rigorously justify a singular approximation of the incompressible Euler equations via a quasi-neutral regime.